2014
DOI: 10.1002/lary.24664
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hypotension, cerebral flow, and the surgical field during endoscopic sinus surgery

Abstract: Hypotensive anesthesia is an effective method of controlling intraoperative bleeding during endoscopic sinus surgery; however the effect is clinically small in low MAP ranges. In otherwise healthy patients undergoing ESS with general anesthesia, reducing MAP to below 60 mm Hg may increase the risk of cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 58 publications
(185 reference statements)
0
23
0
Order By: Relevance
“…A recent study evaluating the patients undergoing hypotensive anesthesia for ESS found that reducing MAP improved bleeding scores, a strong association with reduction of middle cerebral artery blood flow velocity (Vmca) as measured by transcranial Doppler ultrasonography [21]. The results from this study suggested that based on Vmca flows, reducing MAP below 60 mmHg may increase cerebral ischemia risk.…”
Section: Discussionmentioning
confidence: 56%
“…A recent study evaluating the patients undergoing hypotensive anesthesia for ESS found that reducing MAP improved bleeding scores, a strong association with reduction of middle cerebral artery blood flow velocity (Vmca) as measured by transcranial Doppler ultrasonography [21]. The results from this study suggested that based on Vmca flows, reducing MAP below 60 mmHg may increase cerebral ischemia risk.…”
Section: Discussionmentioning
confidence: 56%
“…The small difference in outcomes seen between these studies is likely due to the relative distribution of time points across each MAP range. In Ha et al’s study, almost two‐thirds of all time points resided at low MAPs, resulting in an overrepresentation of time points outside the cerebral autoregulatory range. Data collected within this study showed a wider distribution, such that a greater proportion fell within the autoregulatory range where changes in MAP are expected to produce a less pronounced change in V mca .…”
Section: Discussionmentioning
confidence: 92%
“…A similar value was found in a recent study. Ha et al (2014) demonstrated in 32 patients across a 28 to 124 mmHg MAP range that the relationship between MAP and V mca as measured using TCD, was r = 0.77 ( p < 0.0001). The small difference in outcomes seen between these studies is likely due to the relative distribution of time points across each MAP range.…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic stability provided by intraoperative remifentanil may reduce blood loss (Degoute et al 2001). Several studies have reported reduced blood loss in spinal surgery, rhinoplasty, and endoscopic sinus surgery (Komatsu et al 2007;Kawano et al 2013;Ha et al 2014;Kosucu et al 2014;Cardesin et al 2015). Those studies indicated that hemodynamic stability derived from intraoperative remifentanil use contributed to reduced blood loss.…”
Section: Introductionmentioning
confidence: 99%
“…In endoscopic surgery, even a small amount of bleeding interferes with the visual field; therefore, a reduction in bleeding is essential to facilitate a smooth and successful procedure. However, the reduced blood loss provided by remifentanil in endoscopic surgery has only been reported for otolaryngology procedures such as rhinoplasty and sinus surgery (Ha et al 2014;Kosucu et al 2014;Cardesin et al 2015;Rodriguez Valiente et al 2013). It is unknown whether there is a relationship between the use of intraoperative remifentanil and blood loss in other types of endoscopic surgery such as endoscopic body surface surgery.…”
Section: Introductionmentioning
confidence: 99%